Prediction of self-efficacy, anxiety and decision-making styles on the academic achievement - Murdaca, Anna Maria; Nuzzaci, Antonella; Oliva, Patrizia; Cuzzocrea, Francesca (Formazione & insegnamento, 2014)
The purpose of this study was to examine the effects of some selected variables (problem solving skills, efficacy beliefs, state/trait anxiety, test anxiety, decision-making styles and personality traits) on the achievement of undergraduate students. Participants were enrolled in the first year of the Bachelor’s degree in Psychological Sciences and Techniques of the University of Messina and completed self-report questionnaires. The results showed that decision making styles have a greater impact on student performance, but also anxiety levels and emotional states during exams seem to play a significant predictive role in structuring study outcomes. This confirms the need to focus the attention of educational research, as well as cognitive and metacognitive factors traditionally linked to the learning process, on individual, emotional, and motivational aspects that seem to be strongly related to academic success, influencing the quality of study career.